Development of Football Tactics and Strategies Driven by Artificial Intelligence - Beygmohammadloo, Vahid; Gharakhani, Davood; Naderinasab, Mahdi (AI and Tech in Behavioral and Social Sciences, 2024)
Artificial Intelligence (AI) is revolutionizing the field of sports, especially football, by transforming how game tactics and strategies are developed and implemented. This review examines the integration of AI technologies in football’s tactical and strategic areas, underscoring the significant advancements made recently. AI’s ability to swiftly process extensive datasets with remarkable accuracy provides a significant edge, enhancing the decision-making capabilities of coaches and players. This includes the use of predictive analytics to utilize both historical and real-time game data, which helps predict opponents’ strategies and refine in-game tactics. AI also plays a crucial role in optimizing training schedules and match-day strategies through the simulation of various game scenarios and calculation of outcome probabilities, aiding in strategic planning. This review adopted a systematic approach to assess relevant studies, incorporating a detailed search of electronic databases with terms such as "artificial intelligence," "football tactics," "sports analytics," and "machine learning in sports." This search focused on literature from the past decade, specifically targeting empirical studies that demonstrate AI’s application in football strategy and tactics. Findings from these studies indicate a profound impact of AI on sports analytics, resulting in more informed and dynamic tactical decisions. Moreover, the review explores broader implications of AI in sports, addressing ethical considerations and discussing the potential future of these technologies in professional football. By enhancing strategic understanding and execution, AI not only improves current practices but also paves the way for future innovations in sports strategies. The integration of AI into football tactics has become a central component of the strategic operations of competitive teams, indicating a shift towards more technologically integrated approaches in sports.